Telaah Konsep Tasawuf Syeikh Yusuf Khatar Muhammad dalam Kitab Mausu’ah Yusufiyyah fi Bayani al Adilati as Sufiyyah - Ridha, Arif (Al-Jadwa: Jurnal Studi Islam, 2021)
Sufism is a pure teaching originating from the Islamic religion, with roots in the Al-Qur'an and the hadith of the Prophet Muhammad SAW. This teaching emphasizes spiritual experience, the search for love, and the pleasure of Allah. Scholars agree that Sufism is an additional dimension in Islam that strengthens the personal relationship with Allah. The first scholar to be named "Shufi" was Imam Abu Hasyim from Kufa, followed by Imam Dzu An-Nun Al-Mishri and Imam Al-Junaid Al-Bahgdadi as the developer and expounder of the views of tasawwuf. Figures like Sayyidina Hudzaifah Ibn Al-Yaman and Sayyidina Salman Al-Farisi are examples of people who have the knowledge of tasawwuf. The science of tasawwuf is considered a faith, morality, sincerity, and da'wah based on the Islamic religion, faith, and doing good with muraqabah and musyahadah. Self-introspection and cleaning the heart from immorality are also emphasized in the teachings of tasawwuf. The main goal of tasawwuf is to win the pleasure of Allah SWT. and live life with asceticism, feel the need for Allah, and avoid worldliness and immorality. Faqr or poverty teaches the awareness that everything one has is meaningless before Allah, so that the heart can be purified from anything that keeps it away from Him. All of this forms a strong foundation for the practice of tasawwuf which continues to be an integral part of the Islamic religious tradition.